Finite frequency H∞control design for nonlinear systems - Zineb Lahlou; Abderrahim EL-Amrani; Ismail Boumhidi (International Journal of Power Electronics and Drive Systems (IJPEDS), 2021)
The work deals finite frequency H∞ control design for continuous time nonlinear systems, we provide sufficient conditions, ensuring that the closed-loop model is stable. Simulations will be gifted to show level of attenuation that a H∞ lower can be by our method obtained developed where further comparison.